2021
DOI: 10.1177/10499091211051667
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Sociodemographic and Hospital-Level Factors Associated With Palliative Care Utilization Among Multiple Myeloma Patients Using the National Inpatient Sample (2016-2018)

Abstract: Background: Several factors are reported to be associated with palliative care utilization among patients with various cancers, but literature is lacking on multiple myeloma (MM) specific factors. MM patients have a high symptom burden and early involvement of palliative could increase their quality of life. We examined factors associated with palliative care utilization among MM patients and explored prevalence trends in palliative care utilization among patients with MM. Methods: Cross-sectional analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
(58 reference statements)
2
11
1
Order By: Relevance
“…While NCI‐CCCs provide a significant benefit in research and funding, all ACs are characterized by their access to research and specialized providers. All categories of ACs also share high patient volumes, improved supportive care, and access to specialized treatments over other facility types 8,11 . Access to autologous stem cell transplant, which is the standard of care in eligible MM patients, is also generally only available at ACs, and many of our patients may either be selected for ACs treatment due to transplant eligibility, or benefiting from early access to transplant 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While NCI‐CCCs provide a significant benefit in research and funding, all ACs are characterized by their access to research and specialized providers. All categories of ACs also share high patient volumes, improved supportive care, and access to specialized treatments over other facility types 8,11 . Access to autologous stem cell transplant, which is the standard of care in eligible MM patients, is also generally only available at ACs, and many of our patients may either be selected for ACs treatment due to transplant eligibility, or benefiting from early access to transplant 9 …”
Section: Discussionmentioning
confidence: 99%
“…All categories of ACs also share high patient volumes, improved supportive care, and access to specialized treatments over other facility types. 8,11 Access to autologous stem cell transplant, which is the standard of care in eligible MM patients, is also generally only available at ACs, and many of our patients may either be selected for ACs treatment due to transplant eligibility, or benefiting from early access to transplant. 9 It is important to emphasize that demographics and socioeconomic factors associated with facility selection may also play a significant role in this survival gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Unfortunately, despite the high symptom burden, prior research has shown that palliative care remains underutilized in patients with MM and that rates of hospitalization and aggressive treatment at EOL are high. [5][6][7] Previous work on EOL in myeloma has been limited by either focusing primarily on inpatient hospitalizations, 7,8…”
mentioning
confidence: 99%